CONTROL AND MONITOR OF PRODUCT FILLING AUTOMATION SYSTEM IN PLC-BASED PACKAGING USING HMI OMRON NB7W-TW00B - Sri Kusumastuti (JAICT, 2022)
This study aims to design and create an automation system for filling products into packaging. PLC CP1E-N30DR-A system can be controlled and monitored via Omron NB7W-TW00B HMI. HMI programming using NB-Designer software. The product used is a steel ball. The number of steel balls is set via HMI.  The HMI screen display consists of inputs: Push Button Start, Push Button Stop, input the number of products in the packaging, packaging sensor, and steel ball sensor; outputs: conveyor and counter display. The test results show that HMI could provide variations in the number of products in the packaging. The present value counter can be displayed on the HMI. The control and monitor automation system of filling the product in the packaging worked well.